Competence Analysis of Students on The Soul of Nationalism in the Era Of the Industrial Revolution 4.0 in Harapan Mulia Private Elementary School - Rizka Purnama Sari; Irfan Dahnial (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
This study aims to instill the values of Nationalism through learning various local cultures that exist in the area around the student's residence. Several surveys of research results show that the sense of nationalism of the Indonesian generation has decreased due to the development of technology and digitalization that has blindly controlled the nation's generation without control. On the other hand, the threat of the entry of cultures from the west that have the potential to be displayed by foreign tourists and the influence of the spectacle that cannot be controlled will undermine the sense of nationalism of the Indonesian generation. Elementary schools as the frontline in anticipating the fading of the spirit of nationalism in the nation's generation need to fight hard in instilling a sense of nationalism in the nation's generation by developing a sense of love for the homeland, proud as an Indonesian nation, willing to sacrifice, accepting pluralism, proud of diverse cultures, social care, respect services of the heroes and prioritizing common interests, one of which is to continue to introduce local culture, learn about Pancasila and its symbols and other programmed activities. From the results of the study, it can be explained that the analysis of the competence of students towards the spirit of nationalism in the era of the industrial revolution 4.0 is still not optimal. Most of the students still have not been able to practice the meaning of the precepts of each item of Pancasila, do not memorize the text of Pancasila and the song Indonesia Raya. Private Harapan Mulia elementary school students memorize western dances, western songs and are more familiar with western cultural styles.